Effects of discontinuous training methods in Colombian combat athletes - Carlos Alberto Agudelo Velásquez; Mariluz Ortiz Uribe (Universidad de Antioquia, 2019)
Objective: To determine the effectiveness of the discontinuous training of the VO2Máx, in a competitive period, in combat athletes who live and train in Medellín-Colombia, with national or international sports level. Method: A convenience sample of 42 subjects was selected: 15 women and 27 men, 21 of them judo athletes, 9 fenders, 6 taekwondo athletes, and 6 fighters, from the selections of Antioquia in the Absolute Category, with age = 21.26 ± 3,98 years, size: 1.69 ± 0.09 m, weight = 65.70 ± 12.05 k, and sports experience of 8.54 ± 4.27 years. They were randomly distributed in two experimental groups and one control group. Experimental groups trained endurance for 4 weeks, with 4 stimuli per week, before the National Games, the maximum sports competition in Colombia. One experimental group trained with the interval method and the other with the intermittent method. The control group did not perform a specific endurance training, maintaining the strength training and the technical-tactical components, similarly to the subjects integrating the experimental groups. Results: Significant differences between the pre-test and the post-test for the intermittent group (p < 0.05), and not for the interval or the control groups, were found. Conclusions: Endurance training, based on the intermittent method, produced significant differences in VO2Máx in combat athletes from Antioquia, during the final phase of its preparation. Likewise, it was found that the number of workouts carried out during a concentrated block of specific endurance training significantly influenced the changes that occurred in VO2Máx.